Kepemimpinan Kepala Madrasah dalam Mengembangkan Budaya Religius di MA. Nurul Huda Al-Banat Situbondo - Khairul Anwar; Farida Ulvi Na’imah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
It is about the importance of leadership of the madrasah headmaster in developing religious culture at the MA Nurul Huda al. This leadership aims to develop the existing of religious culture in the madrasah environment.The objectives of this study are 1) Describing the leadership of the madrasah headmaster in developing religious culture 2) Describing the supporting and inhibiting factors of the headmaster's leadership in developing a religious culture 3) Describing the results of the development of religious culture through the leadership of the head of madrasah.This study is a field research, which is conducted directly with the object of research and the data collection is carried out in the field. With this descriptive qualitative research, the researcher tries to reveal the implementation of the leadership of the madrasah headmaster in developing a religious culture in MA Nurul Huda al-Banat Situbondo. The result of this study is the leadership of the madrasah headmaster in developing religious culture in madrasah is to carry out the leadership role of the headmaster, namely as an educator, manager, administrator, supervisor, leader, innovator, and motivator. The supporting factors are the existence of facilities and infrastructure that support religious activities and the existence of teachers who have deep religious knowledge. The inhibiting factor is that the environment still considers madrasah to be less prestigious than public schools in general, a lack of understanding of the development of religious culture, the lack of role models given by teachers, the influence of technological culture, and the absence of training given by the head of madrasah to teachers in the implementation of religious culture.